The pursuit of novel head and neck cancer biomarkers – tissue and blood expression of chloride intracellular channels family - Bartosz Paweł Wojtera; Kamila Ostrowska; Julia Ostapowicz; Mateusz Szewczyk; Julia Kozikowska; Wiktoria Maria Suchorska; Wojciech Golusiński (PLoS ONE, 2025)
Introduction The chloride intracellular channels (CLICs) engage in cancer pathogenesis and have been considered various cancer biomarkers and therapeutic targets. Preliminary research suggests CLICs may be important players in head and neck squamous cell carcinoma (HNSCC). There is a need for reliable HNSCC biomarkers besides well-known HPV and PD-L1. Aim The study aimed to assess the role of CLICs in HNSCC pathogenesis and as potential disease biomarkers. Methods We compared the CLIC1–CLIC6 genes expression between the HNSCC tumors (n = 99) and the tissue from the free surgical margin (n = 74) at the mRNA level with RT-qPCR and at the protein level with Western Blot. To investigate the role of CLIC1-CLIC6 proteins as potential HNSCC blood biomarkers, we performed the ELISA assays on blood serum from 38 HNSCC patients and eight healthy individuals. Results We found significant differences in the expression of every analyzed CLIC. At the mRNA level, CLIC1 and CLIC4 were overexpressed in oral cancer tissue, CLIC3, CLIC5, and CLIC6 were down-expressed; in laryngeal cancer tissue, CLIC2 and CLIC3 were down-expressed. Tumor staging impacted CLIC1 and CLIC6 tissue expression, and histological grade impacted CLIC6 tissue expression. At the protein level, CLIC3 was down-expressed in oral cancer tissue. Furthermore, CLIC1 and CLIC3 proteins were overexpressed, and CLIC4 and CLIC6 were down-expressed in the oral cancer patients’ blood serum compared to the control group. Conclusion The different expression patterns of CLICs in HNSCC patients’ tissues and blood serum suggest that they may play an essential role in HNSCC pathogenesis and serve as biomarkers for HNSCC detection.